Calcium-binding sites of the thrombin-thrombomodulin-protein C complex: Possible implications for the effect of platelet factor 4 on the activation of vitamin K-dependent coagulation factors - Yang, Likui; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2007)
The Ca2+-dependence of protein C activation by thrombin in complex with thrombomodulin (TM) containing chondroitin sulfate (CS) exhibits saturation at ~0.5–1 mM Ca2+, but withTM lacking CS, it has a distinct optimum at ~0.1 mM Ca2+. Since the substrate protein C has multiple Ca2+-binding sites, and the cofactor TM also interacts with Ca2+, the basis for differences in Ca2+ effect on protein C activation by thrombin in complex with TM containing or lacking CS is not known. In this study, by using full-length and Gla-domainless mutants of protein C whose activation by thrombin is independent of either Ca2+ or both Ca2+ and TM, we demonstrate that i) the Ca2+ occupancy of a high-affinity binding site in TM is essential for the high-affinity interaction of the cofactor with thrombin, ii) the Ca2+ occupancy of a binding site (KD ~50 μM) in the catalytic domain of protein C is required for the substrate recognition by the thrombin-TM complex, however, at this concentration of Ca2+ the Gla domain of protein C is not folded properly and thus interacts with exosite-2 of thrombin in complex with TM that lacks CS but not withTM that contains CS, and finally iii) platelet factor 4 can nonspecifically interact with the Gla domain of protein C and other coagulation factors to influence their activation only at subphysiological concentrations of Ca2+.
Keywords: Thrombomodulin; chondroitin sulfate; protein C; thrombin; calcium; platelet factor 4